Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Pada Toko Euro Sport Surabaya - Siti Fatmala Lailatus Sa’diyah; Iswati Iswati (Jurnal Publikasi Ilmu Manajemen, 2023)
The purpose of this research is to find out and analyze how much influence price and product quality have on customer purchasing decisions at the Euro Sport Store in Surabaya. The method used is quantitative with a descriptive type. The sample for this research was 50 samples using a random sampling technique, while the data analysis method used in this research was multiple regression analysis. The results of the research show that product quality has an influence and significance on Euro Sport Shop purchasing decisions, as can be seen from the calculated t value > t table (4.744 > 1.678), and a lower significant level of 0.05, namely 0.000, price has an influence and significance on Shop purchasing decisions. Euro Sport can be seen from the calculated t value > t table (2.237 > 1.678), and sig 0.030 > 0.05, (Product Quality and Price) has a significant effect on Euro Sport Store Purchasing Decisions seen from the calculated t value > calculated f table > f table 79.992 > 3.195) and a sig value of 0.000 < 0.05, meaning that simultaneously all independent variables have an influence and significance on the related variables, the R square value is 27%. While the rest are variables that were not examined in the research.